Juvenile Spondyloarthritis in the Childhood Arthritis and Rheumatology Research Alliance Registry: High Biologic Use, Low Prevalence of HLA–B27, and Equal Sex Representation in Sacroiliitis. Issue 7 (28th June 2021) - Rumsey, Dax G.; Lougee, Aimee; Matsouaka, Roland; Collier, David H.; Schanberg, Laura E.; Schenfeld, Jennifer; Shiff, Natalie J.; Stoll, Matthew L.; Stryker, Scott; Weiss, Pamela F.; Beukelman, Timothy
Abstract : Objective: To describe characteristics of children with enthesitis‐related arthritis (ERA) and juvenile psoriatic arthritis (PsA) who were enrolled in the Childhood Arthritis and Rheumatology Research Alliance (CARRA) registry. Methods: All children with ERA and those with juvenile PsA were identified. Demographic characteristics, clinical characteristics, and treatments were described. The children with sacroiliitis and those without sacroiliitis were compared. In the children with sacroiliitis, the first visit with clinically active sacroiliitis (which came first in 72% of cases) was compared to the first visit without clinically active sacroiliitis. Results: A total of 902 children with ERA or juvenile PsA were identified. Children with ERA were older at diagnosis (ages 10.8 years versus 8.2 years; P < 0.01) and were more likely to be male (56% versus 38%; P < 0.01). Polyarticular involvement was reported in 57% of children with ERA and in 72% of those with juvenile PsA. Of the children tested, HLA–B27 was positive in 38% of those in the ERA group and in 12% of those in the juvenile PsA group. At least 1 biologic was taken by 72% of those with ERA and 64% of those with juvenile PsA. Sacroiliitis (diagnosed clinically and/or by imaging) was reported in 28% of the children (40% of those with ERA and 12% of those with juvenile PsA). Of these, 54% of the children were female, 36% were HLA–B27 positive, and 81% took at least 1 biologic. In children with sacroiliitis, scores according to the physician global assessment of disease activity, parent/patient global assessment of well‐being, and clinical Juvenile Arthritis Disease Activity Score 10 were all significantly worse at the first visit with clinically active sacroiliitis versus the first visit without active sacroiliitis. Conclusion: In this registry, there are more than 900 children with ERA or juvenile PsA. There was high biologic use in this population, especially in those with sacroiliitis. Further, there was equal sex representation in those children with sacroiliitis.